Current medical treatment in pediatric urolithiasis - Akın, Yiğit (Turk J Urol, 2013)
Although the prevalence of urolithiasis is nearly 2–3% in childhood, the risk of recurrence may range from 6.5–54%. There has been an increase in urinary stone disease among pediatric age groups, and stone disease has a multifactorial etiology. After the diagnosis, detailed metabolic evaluation is required. High recurrence rates, therapeutic irregularities and deficiency in diagnosis may lead to comorbidities such as loss of kidney function. Following diagnosis, the requirement for surgery, such as stone extraction and correction of anatomical anomalies, is determined. Medical and supportive treatments are also needed to prevent recurrence and urinary tract infections and to preserve renal function. Supportive care includes increased fluid intake and dietary modifications. Medical treatment is dependent on the cause of the urinary stone disease. The morbidities associated with pediatric urolithiasis can be prevented by early diagnosis, detailed metabolic analysis, regular follow-up and medical treatment protocols.